Effect of phosphorus fertilizer on nodulation, growth and yield of cowpea (Vigna unguiculata) varieties - OKELEYE, K A; OKELANA, M A O (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted fOf 2 years (1991 and 1992) at Abeokuta, south-west of Nigeria, to investigatc theeffect of phosphorus application (0, 30 and 60 kg P/ha) on nodulation, dry-matter accumulation and grain yield of 6newly developed varieties of cowpea [Vigna unguiculata (L.) Walp.1, viz 'IT 86D-I038', 'IT 86D-4982', 'IT 82D-699'IT 86D -27', 'IT 86D-444' and 'IT 81D-1228'). Nodulation increased significantly in 'IT 86D-1038' from 202 at 0 kgPlha to 225 at 30 kg P/ha. This significantly increased, the nodulation in other varieties too at 0-30 kg P/ha. Higher rateof P (60 kg P/ha) resulted in significantly higher nodulationÂ  in 'IT 82D-699' (184) and 'IT 86D-444' (188). The high Prate significantly reduced the number of days to 50%Â  flowering by 5-8 days. The number of days to 50% flowering, unlike grain yield, was inversely related to P level in all the varieties. The grain yield of ' IT 86D-1038' was I 082 kg/ha at 0 kg P/ha and 2 288 kg/ha at 60 kg/ha. Similar increase in yield was noted in other varieties tested, except in 'IT 86D-444'. which gave its highest average yield of 2 423 kg/ha at 30 kg P/ha that decreased to 2 306 kg/ha at 60 kg P/ha.